Biologics Versus JAK Inhibitors. Part II: Risk of Infections. A Narrative Review - Miguel Mansilla-Polo; Daniel Morgado-Carrasco (Adis, Springer Healthcare, 2024)
Abstract Introduction The risk of infections associated with biological drugs (BD) and Janus kinase inhibitors (JAKi) has been extensively explored in the literature. However, there is a dearth of studies that evaluate both pharmacological groups together and, furthermore, compare them. Here, we review the risk of infections associated with BD and JAKi used in dermatology. Methods A narrative review was performed. All relevant articles evaluating the risk of infection and opportunistic infections with BD and JAKi between January 2010 and February 2024 were selected. Results Overall, the incidence of infections, serious infections, and opportunistic infections associated with BD and JAKi is low, but higher than in the general population. JAKi approved for dermatological disorders (abrocitinib, baricitinib, deucravacitinib, upadacitinib, ritlecitinib, and topical ruxolitinib) have been shown to be safe, and present a low rate of infections. We found an elevated risk, especially with anti-tumor necrosis factor (anti-TNF) agents, rituximab, and JAKi (particularly tofacitinib at high doses). Specific associations with infections include tuberculosis and tuberculosis reactivation with anti-TNF agents and tocilizumab; candidiasis with anti-interleukin (IL) 17 agents; hepatitis B virus reactivation with rituximab, anti-TNF, and JAKi; and herpes simplex and herpes zoster infections with JAKi (especially tofacitinib and upadacitinib at high doses). The incidence of infections with ustekinumab and anti-IL-23 was very low. Anti-IL-1, nemolizumab, tralokinumab, and omalizumab were not associated with an increased risk of infections. Dupilumab could decrease the incidence of cutaneous infections. Conclusions Anti-TNF agents, rituximab, and JAKi (particularly tofacitinib) can increase the risk of infections. Close monitoring of patients undergoing these therapies is recommended. Prospective studies with long-term follow-up are needed to comparatively evaluate the risks of infection deriving from treatment with BD and JAKi.